Do Oversubscribed IPOs Perform Better in the Long Run? Evidence from the Emerging Economy of India - Kumar, Anil; Totla, Madhu (Indian Journal of Finance, 2023)
Purpose : The study aimed to broaden and contextualize the emerging knowledge about the impact of initial public offerings (IPOs) on the operating performance and financial health of public firms in India and whether oversubscription and underpricing of the IPO firms determined the change in performance. Design : It entailed the comparison of pre-IPO and post-IPO performance for 3 years by employing data from 95 IPO firms getting listed on the main board segment of NSE and BSE in India between April 2012 and March 2018. Methodology : The methodology consisted of both univariate and multivariate data analysis techniques. Multivariate regression analysis determined whether underpricing and subscription levels determined IPO firms’ post-issue long-run operating performance. Findings : The study suggested that operating performance dropped significantly while financial health improved post-IPO. Both oversubscription and underpricing were not predicting factors of change in performance post-IPO. Rather, issue size, offer price, and post-issue promoter holding significantly and negatively impacted the change in performance ; whereas, age positively and significantly determined the change in performance after the IPOs. Practical Implications : The study recommended that, with the indication of earnings management being done just before the IPOs, investors need to exercise caution in relying on the financials immediately before the IPO. The findings of the study will guide investors in making accurate investments in the primary and secondary equity markets. Originality : Unlike previous research, this study examined the impact of IPOs on the firms’ financial health post-issue and whether subscription to IPOs determined the change in performance of new listings on the main board segment in India.